Éperons : les styles de Nietzsche - Derrida, Jacques 1930-2004; Agosti, Stefano 1930-; Loubrieu, François 1948- (Paris Flammarion, 1978)
Nietzsche has enjoyed much scrutiny from the nouveaux critiques. Jacques Derrida, the leader of that movement, here combines in his strikingly original and incisive fashion questions of sexuality, politics, writing, judgment, procreation, death, and even the weather into a far-reaching analysis of the challenges bequeathed to the modern world by Nietzsche.
Keywords: Nietzsche, Friedrich Wilhelm -- 1844-1900; Philosophy; Feminism